2018
DOI: 10.1038/s41598-017-18822-9
|View full text |Cite|
|
Sign up to set email alerts
|

Localization and function of neurosecretory protein GM, a novel small secretory protein, in the chicken hypothalamus

Abstract: Recently, we discovered a novel cDNA encoding the precursor of a small secretory protein, neurosecretory protein GL (NPGL), in the hypothalamic infundibulum of chickens. NPGL plays an important role in the regulation of growth and feeding. A database search indicated that the NPGL gene has a paralogous gene: neurosecretory protein GM (NPGM), also in chickens. We identified cDNA encoding the NPGM precursor in chickens. Morphological analysis showed that NPGM-containing cells are specifically localized in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Furthermore, homologous NPGL proteins have been discovered in mammals, including humans, rats, and mice, suggesting that the primary structure of NPGL is highly conserved in mammals and avian species [ 20 ]. In addition, its paralogous neuropeptide has been identified and named neurosecretory protein GM [ 21 ]. Similar to the effects of NPGL infusion on energy metabolism in avian species [ 22 , 23 ], acute intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, homologous NPGL proteins have been discovered in mammals, including humans, rats, and mice, suggesting that the primary structure of NPGL is highly conserved in mammals and avian species [ 20 ]. In addition, its paralogous neuropeptide has been identified and named neurosecretory protein GM [ 21 ]. Similar to the effects of NPGL infusion on energy metabolism in avian species [ 22 , 23 ], acute intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we discovered two novel cDNAs (viz., neurosecretory protein GL ( Npgl ) and its paralog neurosecretory protein GM ( Npgm )) that encode the precursors of NPGL and NPGM, respectively, in chicken, rat, mouse, and human brains [ 29 , 30 , 31 , 32 ]. We revealed that NPGL is expressed in the mediobasal hypothalamus (MBH) of mouse and rat brains and promotes feeding and fat accumulation [ 30 , 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…We revealed that NPGL is expressed in the mediobasal hypothalamus (MBH) of mouse and rat brains and promotes feeding and fat accumulation [ 30 , 31 , 33 ]. It is likely that NPGM has a similar biological function because both neurosecretory proteins are produced in the same neuron [ 32 ]. However, whether NPGL and NPGM are involved in the biological rhythm of feeding behavior and energy metabolism has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we discovered a novel cDNA encoding the precursor of a small secretory protein in the chick hypothalamus (Ukena et al, 2014; Shikano et al, 2018a). We named the small protein of the 83-amino acid residues as neurosecretory protein GM (NPGM) (Ukena et al, 2014; Shikano et al, 2018a). The NPGM gene is highly conserved in vertebrates, including chickens, rats, and humans (Ukena et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies identified the localization of NPGM in the chick brain by in situ hybridization and immunostaining. NPGM-producing cells are localized in the infundibular nucleus (IN) and the medial mammillary nucleus (MM) of the hypothalamus in chicks (Shikano et al, 2018a). These nuclei are known to be feeding and metabolic centers in chicks.…”
Section: Introductionmentioning
confidence: 99%